Роль соціальних мереж у формуванні комунікативних та емоційних навичок старшокласників - Гунчак, Олександр,Тетяна Равлюк (My University, 2025)
Modern society, including Ukrainian society, cannot develop without the introduction of innovative information and communication technologies, among which social networks play an important role. Numerous scientific studies emphasize the phenomenon of social networks and their impact on personality, particularly on the development of soft skills. The article defines the concepts of "soft skills" and "social networks"; specifies the structure of "soft skills," including basic, communicative, social, thinking, self-control, and self-esteem skills. The main characteristics of social networks that attract a large number of users are identified. The ranking of the most popular social networks in Ukraine in 2024, according to authoritative services, is analyzed. It is noted that these include Facebook, Instagram, TikTok, and Telegram. The results of a survey conducted by the Public Health Center of the Ministry of Health of Ukraine within the framework of the international project "Health and Behavioral Orientations of School-Aged Youth" are described, revealing the significance of social networks and virtual communication in the daily lives of adolescents. It is stated that social networks are important communication tools for high school students, contributing to the development of their communicative and emotional skills. Interaction in the online environment helps them improve their written and oral communication, argue their own position, adapt their communication style, and effectively interact with others. Social networks can play a significant role in the development of emotional intelligence, helping high school students learn to recognize and express their own emotions, as well as develop empathy. Communication in the online space teaches them to interact, support others, and analyze the emotional expressions of their interlocutors. The possible negative impact on communication skills, the decline in literacy due to slang and abbreviations, superficial perception of information, and the reduction of live communication are noted, as well as the harm to the emotional state of adolescents. A balance between online and offline communication, the development of digital literacy and critical thinking will help adolescents use social networks constructively.
Keywords: soft skills, social networks, communicative skills of high school students, emotional intelligence.